Diferensial Parsial dan Trend Penjualan dalam Analisa Kontribusi Margin untuk Menentukan Sales Mix yang Optimal - Rustam Hanafi (Universitas Wahid Hasyim, 2006)
The research was held to know : (1) How type of each product variable cost which applied in many company (2) How many products that must be sold from each of them for optimal composition (3) how the value of profit optimum. From the research on Dipta Sunrise Nusantara II Company which product many export shoes, was known that that variable cost on each product made square equation or Curve line. From this point, the variable had point optimum which could influence margin contribution. With Differsial Parsial on margin contribution was yield optimum sales for type GOLA shoes 107.156 set, LETOON 107.180 set, UNIVERSE 82.552 set and minimize sales for GOGGI shoes 117.371 set and CATALPA 107.249 set. Maximize sales as the demand for GOGGI was 120.500 set and CATALPA 114.000 set. From the research, we could know that optimum supplier composition from each product to optimum profit were : GOLA 107.156 set, GOGGI 120.500 set, CATALPA 114.00 set, LETOON 107.180 set and UNIVERSE 82.552 set. So total optimum profit from these were Rp 8. 708.080.000,00